2014
DOI: 10.1016/j.gexplo.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Response of Enchytraeus crypticus worms to high metal levels in tropical soils polluted by copper smelting

Abstract: Tropical soils from the vicinity of the Mufulira copper smelter (Zambian Copperbelt) were found to contain high levels of metals, particularly in the upper parts of soil horizons. Metal concentrations varied within the ranges: 37-8980 mg Cu/kg, 3-46 mg Co/kg, b 2.5-42 mg Pb/kg, and 16-83 mg Zn/kg. The EDTA extractions indicated that a considerable percentage of the metals were bound in the "labile" fractions of the soil (up to 55% of total Cu concentration, 36% Co, 41% Pb, 30% Zn). The mineralogical investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…The exchangeable base cations such as calcium (Ca 2þ ), magnesium (Mg 2þ ), sodium (Na þ ) and potassium (K þ ) are associated to effect the CEC values of soil (Rayment and Higginson, 1992) and our earlier study shows a high level of calcium and sodium in mine soil at the same location (Nirola et al, 2015). However, our present study does not show much effect of pH and CEC on earthworm metal uptake, a finding similar to Konecny et al, 2014. With regards to higher electrical conductivity (EC) as in treatments 3 and 4 (CHF and MHF respectively), soil salinity seems to have facilitated bioavailability of metals (Owojori et al, 2008).…”
Section: Bioavailable Metal and Bioaccumulationsupporting
confidence: 85%
See 1 more Smart Citation
“…The exchangeable base cations such as calcium (Ca 2þ ), magnesium (Mg 2þ ), sodium (Na þ ) and potassium (K þ ) are associated to effect the CEC values of soil (Rayment and Higginson, 1992) and our earlier study shows a high level of calcium and sodium in mine soil at the same location (Nirola et al, 2015). However, our present study does not show much effect of pH and CEC on earthworm metal uptake, a finding similar to Konecny et al, 2014. With regards to higher electrical conductivity (EC) as in treatments 3 and 4 (CHF and MHF respectively), soil salinity seems to have facilitated bioavailability of metals (Owojori et al, 2008).…”
Section: Bioavailable Metal and Bioaccumulationsupporting
confidence: 85%
“…In a study of Konecny et al, 2014 on Enchytraeus crypticus, there was no reproduction in soils with Cu levels >5000 mg/kg. Moreover, the reproduction effect concentration (EC50) was 351 mg/kg, a value within the range of our treatments.…”
Section: Discussionmentioning
confidence: 98%
“…Despite of the above-mentioned difficulties in interpreting the results of earthworm tests in field-collected soils, Konečný et al (2014) were successful in determining a metal of prime concern and metals with additional toxic effects to earthworms, in soils containing various metals. Likewise, Nahmani et al (2007a) identified metals that caused toxicity to earthworms exposed to soils containing various metals, based on analysis of metal concentrations in earthworm tissues.…”
Section: Introductionmentioning
confidence: 99%
“…; Konečný et al . ). Soil fauna may assist with pathogen removal, but their role has not yet been evaluated in these systems.…”
Section: Functional Effects Of Faunamentioning
confidence: 97%